Volatile agents and renal transplantation - Kemal Tolga Saracoglu; Beliz Bilgili; Ayten Saracoglu (Global Journal of Anesthesiology - Peertechz Publications, 2020)
Living donor and cadaveric donor renal transplantation have received a significant interest. During the procedure, both volatile agents and total intravenous anesthesia are used.  However, the effects of volatile agents used during anesthesia on primary graft dysfunction is controversial. Besides evidence-based scientific data is not enough to conclude the ideal inhalation agent in renal transplantation. This review aimed to determine the effects of volatile agents preventing or improving the Ischemia Reperfusion (IR) injury during general anesthesia in patients undergoing renal transplantation. The possible mechanisms that affect the outcome of the patients after transplantation will be discussed.